Evaluating the plant community patterns in Mantanani Besar Island using GIS and phytosociological survey - Yuta Inaguma; Johnny Gisil; Charles Santhanaraju Vairappan; Liew Thor Seng (Forest Research Institute Malaysia, 2025)
Mantanani Besar Island, in Kota Belud, Sabah, Malaysia, is both a tourist site and an important ecological site for many species. Despite the ecological importance, information on the distribution of plant species remains limited. This study aims to fill this gap by examining community patterns using vegetation mapping and a phytosociological survey. Based on our spatial analysis, approximately 84% of this island’s surface area is covered by forests, categorised into two distinct types: inland and coastal forest. Further investigation based, 55 quadrat plots (10m × 10m) that were randomly established in the classified forested area confirmed 66 species, representing 63 genera and 38 families. Two of the 66 recorded species were listed in the IUCN and Malaysia Plant Red Lists. The ANOSIM and Mantel’s tests revealed four plant community types in the island’s forested areas. Our survey the first comprehensive plant species checklist and community patterns on the island. We also concluded that combining both methods is beneficial for designing vegetation mapping.